Simulation of a Steel Wire Straightening Taking into Account Nonlinear Hardening of Material - Khromov, I.; Kawalla, R. (Engineering, Technology & Applied Science Research, 2012)
Straightening is used to ensure the straightness of a rod workpiece as well as to redistribute or reduce the residual stresses in a finished product. The accuracy of modeling the operation of this kind plays an important role when manufacturing high quality ropes and cables of a small diameter. The physical model of alternating wire bending in a straightener has been considered in the paper. Computer methodology has been developed to calculate deflected mode and internal bending moment in a cross section of a wire at the different stages of deformation, which allowed taking into account nonlinear hardening of the material.